2012
DOI: 10.1523/jneurosci.5996-10.2012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants ofFOXP2andKIAA0319/TTRAP/THEM2Locus Are Associated with Altered Brain Activation in Distinct Language-Related Regions

Abstract: Recent advances have been made in the genetics of two human communication skills: speaking and reading. Mutations of the FOXP2 gene cause a severe form of language impairment and orofacial dyspraxia, while single-nucleotide polymorphisms (SNPs) located within a KIAA0319/TTRAP/THEM2 gene cluster and affecting the KIAA0319 gene expression are associated with reading disability. Neuroimaging studies of clinical populations point to partially distinct cerebral bases for language and reading impairments. However, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
185
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(201 citation statements)
references
References 71 publications
(118 reference statements)
8
185
1
3
Order By: Relevance
“…In the field of human neurogenetics, a brief (non-systematic) search through literature published between January 2012 and May 2013 identified 13 studies in which left-handedness was applied as an exclusion criterion [33][34][35][36][37][38][39][40][41][42][43] . Some of these studies focused on questions in cognitive neuroscience but included genetic variation as one variable of interest -an increasingly popular approach in human neuroscience research.…”
Section: Origins Of Handednessmentioning
confidence: 99%
“…In the field of human neurogenetics, a brief (non-systematic) search through literature published between January 2012 and May 2013 identified 13 studies in which left-handedness was applied as an exclusion criterion [33][34][35][36][37][38][39][40][41][42][43] . Some of these studies focused on questions in cognitive neuroscience but included genetic variation as one variable of interest -an increasingly popular approach in human neuroscience research.…”
Section: Origins Of Handednessmentioning
confidence: 99%
“…It may therefore be possible to make connections between genetic variation, brain structure and function, and linguistic performance. Interestingly, several studies have reported evidence that some of the putative risk variants for language-related disorders have detectable effects in the brains of unaffected individuals (Scerri et al 2012;Pinel et al 2012;Whalley et al 2011;Dennis et al 2011;Tan et al 2010;Scott-Van Zeeland et al 2010;Kos et al 2012;Darki et al 2012), but see Hoogman et al 2014. Neurobiological endophenotypes may enable identification of components of the genetic infrastructure underlying language that cannot be discovered using only behavioral measures.…”
Section: Phenotypes In Genetic Studies Of Languagementioning
confidence: 99%
“…However, such results should be viewed with caution because migration deficits from in utero knockdown in rats do not appear to be supported by investigations in other systems, such as gene knockouts in mice (e.g., see Wang et al 2011) and there is new evidence suggesting that the knockdown methodology is susceptible to off-target effects (Baek et al 2014). Effects of risk variants on human brain anatomy and function have also been suggested by imaging and electrophysiological studies, although (as noted above) sample sizes for the relevant studies have been small and underpowered, so independent replication is still needed (Scerri et al 2012;Pinel et al 2012;Cope et al 2012;Lamminmaki et al 2012;Whalley et al 2011;Dennis et al 2011;Tan et al 2010;Scott-Van Zeeland et al 2010;Kos et al 2012;Darki et al 2012). …”
Section: Stutteringmentioning
confidence: 99%
“…Certain dyslexia‐related potential endophenotypes affected by genetic risk variants have been reported in neuroimaging studies analyzing specific hemodynamic brain activation patterns. Exemplarily, SNPs in FOXP2 were associated with fMRI activation in the left inferior frontal and precentral gyri, whereas SNP rs17243157 in THEM2 was associated with asymmetry in the functional activation of the superior temporal sulcus (Pinel et al., 2012). Furthermore, Darki, Peyrard‐Janvid, Matsson, Kere, and Klingberg (2012) reported gray and white matter variation to be linked with variants within DYX1C1 , DCDC2, and KIAA0319 dyslexia candidate genes, while Scerri et al.…”
Section: Introductionmentioning
confidence: 99%